PENGARUH PERSEPSI PENGUNJUNG PADA HARGA TIKET MASUK TERHADAP KEPUTUSAN BERKUNJUNG KEMBALI KE TAMAN MARGA SATWA DAN BUDAYA KINANTAN (TMSBK) - Rozi Yuliani (LPPM Universitas Muhammadiyah Sumatera Barat, 2017)
Based on data from the Provincial Tourism Office of Bukittinggi Kinantan park visitors continues to increase every year. Price as a consideration in the purchase decision of a product in this case the decision to return visit to TMSBK The purpose of this study to determine the effect of TMSBK admission price to the decision to return visit to TMSBK. This research method is a survey research. This type of research is descriptive quantitative. The independent variable in this study is the price of admission, the dependent variable is the decision to come back to TMSBK. Sampling technique is Non Probability Sampling accidental sampling is convenience sampling. TMSBK visitors who had previously visited the TMSBK at least one time. Data collection techniques with interviews, questionnaires using Likert Scale. Statistical analysis techniques to test the validity and reliability, analytical description of the variables, the classical assumption test, correlation analysis, regression analysis and hypothesis testing t test and F test (SPSS 20.0 for windows). H1: There is a price of admission TMSBK effect to the decision to return visit to TMSBK. H2: There is the influence of TMSBK admission price to the decision to return visit to TMSBK. The results obtained; price of admission (X1) significant influence on the decision to return visit to the TMSBK. Advised the manager to improve the image of both TMSBK improve services and maintain the quality of tourism products. To increase revenue, the manager may propose increases in the price of admission to the range of Rp. 5,000 to 10,000, -. Need to do further research on other factors that have more influence over decision-making to return visit to TMSBK